PERFORMANCE OF PT MADUBARU PG MADUKISMO BY USING BALANCED SCORECARD APPROACH - Khairani, Lathifah; Waluyati, Lestari Rahayu; Suryantini, Any (Jurnal Aplikasi Manajemen, 2019)
PT Madubaru PG Madukismo is a company engaged in the field of sugar cane agro-industry in Yogyakarta province. Achievement in running a company can be seen from the performance of the company. Performance PT Madubaru overall company can contribute to developing the company in achieving the vision. A Balanced Scorecard is a management tool that can be viewed and maintained a balance between financial indicators (financial perspective) and non-financial indicators (customer, Bisnisinternal process, growth, and learning). The purpose of this study was to determine the performance of PT Madubaru PG Madukismo and formulate alternative strategies improving the performance of PT Madubaru. Data analysis and processing tools used the method of Pairwise Comparisons and Balanced Scorecard. The measurement results show the performance of PT Madubaru PG Madukismo, including very healthy (AA) with a value of 87.81%. Thus it has shown its best performance according to the vision, mission, and strategy of the company.